(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
Acharya Charak by "Pareekshyakaarino Hi Kushala Bhavanti” emphasizes the importance of examinations in all aspects of life and equates examination with knowledge. Examination is not possible without knowledge and neither is knowledge possible without examination. Our Acharyas from the very beginning have renovated Ayurveda obtained from Indra in the Rishi Sabhas by re-examination of the miserable condition of the diseased, examination of Ayurveda and appropriate Acharya with the eye of knowledge. The interest of Ayurveda mystics towards the examination is evident from the description provided. The knowledge of Samhitas includes various examinations related to health, disease, patients, diet, drugs, and age. These examinations cover pre-natal, gestational, and newborn assessments along with the examination of the age which is divided into two parts. One is a test of the entire age and the other is the evaluation of the remaining age for both a healthy person and patient. Its general examination can be done by Prakriti and Vikriti and in the special examination separate special expressions called Parikshya Bhavas have been examined. Acharyas have also described a method of examining the affected person’s senses, Chaya and Prabha to determine the extent to which they are unable to function properly. Aim & Objective: Study the parameters and processes of the examination described in detail in the Indriya Sthana and use it in health and medical science. Method: An in-depth study & analysis of Indriya Lakshanas from Brihatrayi along with their commentaries was done as a departmental study project. Conclusion: Examining the expressions mentioned in the context of Arishta Pariksha benefits in health, disease and death knowledge.